Permohonan Wali ‘A?al Karena Wali Meminta Mahar Yang Memberatkan (Studi Putusan Pengadilan Agama Blora Nomor: 0421/Pdt.P/2020/PA.Bla) - Zulfati, Nisrinah (Bulletin of Community Engagement, 2024)
A marriage is invalid if there is no guardian, but the reality is that not all guardians want to be the guardian of the marriage, there are guardians who are reluctant to marry their children or are called guardians 'a?al. As happened at the Blora Religious Court in 2020, the Applicant registered his marriage at the Blora City KUA but was rejected because the guardian 'a?al on the grounds that the guardian asked for an incriminating dowry. The Applicant submitted an application for a guardian judge to the Blora Religious Court to designate the Applicant's father as the guardian of 'a?al and appoint a guardian judge to marry her. The type of research used is normative legal research with a legislative approach (statue approach) and a case approach, namely by studying the application of legal norms and rules in legal practice. The data source comes from interviews with the judge who decides the case of wali 'a?al and the secondary source is sourced from the judge's decision data Number: 0421/Pdt.P/2020/PA. Bla at the Blora Religious Court. The data collection methods used are interviews and documentation methods. Data analysis used by descriptive analytical methods and data triangulation analysis. The results of this study conclude that the decision of the Blora Religious Court judge is appropriate when viewed and analyzed based on the articles and postulates used. Dowry cannot be used as a reason for a guardian to be reluctant to marry his child. The analysis method used in formal legal analysis is seen from 3 (three) processes, namely trial preparation, trial examination and decision-making by the judge through 3 (three) stages, namely constituting (proof), qualifying events or facts (assessment), and constituting (determination). Material legal analysis of the value of legal certainty, the value of procedural justice, and the value of utility. Keywords: Marriage, Wali 'A?al, Wali 'A?al's Application